Predictors of arterial hypertension in children (A Review) - A. V. Burlutskaya; O. G. Korobkina (Кубанский научный медицинский вестник, 2020)
Background. Arterial hypertension poses a relevant problem and roots in early childhood. Today, arterial hypertension in children and adolescents is considered rather common and should be controlled and prevented as early as possible, which warrants further research into its pathogenesis and effective correction.Objectives. To generalize current knowledge of microbiota in the development of arterial hypertension in children.Methods. National and foreign published sources were surveyed in the eLibrary, Web of Science and PubMed databases. Keyword queries were: gut microbiota, arterial hypertension [артериальная гипертензия], children [дети], chronic systemic inﬂammation [хроническое системное воспаление], probiotics [пробиотики]. All sources have a publication depth of 7 years. The study used content analysis and descriptive analytics.Results. Arterial hypertension remains a problem of high economic, medical and social importance as a major cause of brain disorders and coronary heart disease. Hypertension is shown to emerge early in childhood and adolescence during the regulatory network formation. Manifold evidence is accumulated on the involvement of human microbiota in pathogenesis of arterial hypertension. Infant microbiota is more unstable than in adults. Its taxonomic proﬁle is viewed important for sustaining health, with imbalances in intestinal microbiota potentially entailing serious consequences. The impact of microbiota on chronic systemic inﬂammation, lipid metabolism, development and progression of atherosclerosis has been reported. Certain bacterial strains are known to exert benign effect on arterial hypertension and blood cholesterol. Selected mechanisms of the microbiota-mediated regulation of blood pressure have been identiﬁed. Improved methods for microbial community correction are being developed and include diet, antibiotic, prebiotic and probiotic regimens, faecal microbiota transplant.Conclusion. Current achievements promise the emergence of novel approaches for arterial hypertension control early in childhood to avoid incorrigible adult complications.